THE ANALYSIS OF SOILS POLLUTION WITH PETROCHEMICALS BY THE MEANS OF ELECTROMETRIC METHOD - Radomska, Margaryta Myroslavivna; Nazarkov, Taras Ivanovych; Ponomarenko, Maryna Oleksandrivna (Science-based technologies, 2019)
Petroleum products are one of the most common components of chemical pollution of the environment. They represent a group of pollutants of extremely complex and diverse chemical composition, which complicates their detection and analysis in environmental components. Sources and consequences of soils pollution with petroleum products are considered in the paper, stating that it causes degradation of soil quality and failing to perform environmental functions. The comparative analysis of conventional testing methods of petroleum products in the soil demonstrates their common disadvantages – complicated equipment used or low accuracy of results. The change of electric soil properties under the influence of petroleum pollution is offered to be used as the basis of alternative testing method. The measurement of electrical resistance of soils, typical for the territory of Kyiv, with artificially created petroleum pollution was used to develop model dependencies between concentration of petrochemicals and resistance of pollutes soils. The pollution was modeled with market products – gasoline, diesel fuel and semi-synthetic oil. The soils involved in the research are soddy-podzolic, dark-gray podzolic, gray forest and alluvial. The analysis of the obtained results has demonstrated that major difference in polluted soils resistance is conditioned by the type of soil, but not the type of petrochemical in question. This enables the use of developed models to define the presence of petrochemicals in specific soils, but prevents the exact determination of the pollution composition. The proposed method was tested on real samples of soils taken at fuel filling stations. The comparison of the concentrations determined by electrometric and gravimetric method shows the sufficient reliability of the model dependancies developed, but they must be adapted to the specific soil properties, in particular soil texture, reaction and humidity.